Predicting mobile learning culture model among students of higher learning institutions implications on curriculum design - Hashim, Che Noraini; Syed Hassan, Sharifah Sariah (2015)
There are increasing calls for further improvement with regards to the Malaysian educational curriculum. The technology advancement in computer and communications has changed the culture of communications and learning methods at schools and higher learning institutions. This study explores the use of Mobile Wireless Technology (MWT) among students of higher learning institutions and focused on two objectives, firstly to investigate student responses the social norms that mould their behaviours when using the MWT in learning.The second objective is to predict the model of learning culture where ethics, attitude and social norms affect the use of mobile at higher learning institutions and its implication on curriculum design. A survey was carried out from five universities and one Community college in Malaysia. From each institution, the students were randomly stratified and selected. There were 490 respondents involved in the study. The model has been hypothesized to show the culture of m-learning which implicate the design of curriculum. Specifically the model has been tested to confirm whether all the three factors namely ethics, attitude, and social norms affect student’s use of mobile in learning. The descriptive analysis was used to address the first objective of the study. The second analysis involved Structural Equation Modelling (SEM) in validating the model. The findings show a valid model that explains significant contributions from all predictors on the actual use of MWT in learning. Thus, the findings show the necessity for the educators to include ethical use and behaviour guidelines as the components in the curriculum design.